2018
DOI: 10.33151/ajp.15.2.577
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults’ Perception of Mandatory Cpr Training in Australian High Schools: A Qualitative Investigation

Abstract: IntroductionBystander cardiopulmonary resuscitation (CPR) can be performed by any member of the public who witnesses a cardiac arrest and has the knowledge, training and skills to perform it. Even though bystander CPR has been shown to greatly improve the victim’s chance of survival, its training and performance rates are alarmingly low.MethodsOne potentially effective intervention to tackle this issue is to implement mandatory CPR training programs in high schools. We undertook in-depth qualitative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
(22 reference statements)
4
8
0
Order By: Relevance
“…Our investigation found that recent high school graduates were strongly supportive of introducing mandatory CPR training in high school education. This is consistent with a qualitative study of recent high school graduates in Western Australia, 9 and also mirrors the reception found in secondary school students in Norway, a country that already has mandatory CPR training in its high school curriculum 8 . Our data suggests not only that there would be little‐to‐no resistance from high school students in implementing mandatory CPR training in their high school education, but also that most students would welcome the concept.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our investigation found that recent high school graduates were strongly supportive of introducing mandatory CPR training in high school education. This is consistent with a qualitative study of recent high school graduates in Western Australia, 9 and also mirrors the reception found in secondary school students in Norway, a country that already has mandatory CPR training in its high school curriculum 8 . Our data suggests not only that there would be little‐to‐no resistance from high school students in implementing mandatory CPR training in their high school education, but also that most students would welcome the concept.…”
Section: Discussionsupporting
confidence: 89%
“…Our data suggests not only that there would be little‐to‐no resistance from high school students in implementing mandatory CPR training in their high school education, but also that most students would welcome the concept. Another significant benefit to implementing mandatory CPR training is addressing socioeconomic bias in CPR training provision, given that cost has been identified as one of the limiting factors of accessing CPR training 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations